2016
DOI: 10.20885/ejem.vol8.iss2.art7
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and competitiveness of Indonesia’s palm oil export in India market

Abstract: This study examines the elasticity and competitiveness of Indonsia's palm oil export in the India market, 1990India market, -2014. The methods used are Error Correction Model (ECM) and Revealed Comparative Advantage (RCA) approach. The results shows that the price is inelastic in short-term but it is elastic in long-term. The income and exchange rate are elastic in the long-term. There is also a decline in competitiveness in the market India. These findings also demonstrate that palm oil is normal goods and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
9
0
5
Order By: Relevance
“…This result reveals a comparative advantage of a country in international trade (Hillman, 1980;Bender & Li, 2002). There are many empirical studies on trade, especially for palm oil commodities, that devote to the analysis of comparative advantage that based on RCA (Arip et al, 2013;Dewanta et al, 2016). Following those previous studies, RCA calculation method is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…This result reveals a comparative advantage of a country in international trade (Hillman, 1980;Bender & Li, 2002). There are many empirical studies on trade, especially for palm oil commodities, that devote to the analysis of comparative advantage that based on RCA (Arip et al, 2013;Dewanta et al, 2016). Following those previous studies, RCA calculation method is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Despite the huge total of CPO exports to India, research by (Dewanta, Arfani, & Erfita, 2016) resulted that there is a decline in the competitiveness of Indian's market. It is also said that CPO is normal goods and can be easily substituted with the same product from other countries or other vegetable oils.…”
mentioning
confidence: 99%
“…Many writers raised the material on biodiesel exports, but only a few authors wrote the competitiveness of biodiesel. Dewanta et al (2016) concerning the elasticity and competitiveness of the Indonesian commodity in the Indian market but commodity was palm oil and Pambudi et al (2019) concerning the determinants of biodiesel exports in Indonesia, and no writings were found that wrote the competitiveness of Indonesia's biodiesel exports on the Spanish or EU markets. So be convinced that this paper is different from previous papers.…”
Section: Previous Research and Noveltymentioning
confidence: 99%